Construction waste management of Malaysia: case study in Penang - Shan, Ng Lee; Wee, Seow Ta; Wai, Tan Lai; Chen, Goh Kai (American Scientific Publishers, 2018)
Rapid continual development of construction industry has produced large volumes of construction waste. It is filling up the landfill. Disposal of construction waste is an easy and inexpensive approach compares to any 3R practice. In long term, landfills will not be able to accommodate the large volumes of construction waste which reduces the lifetime of landfill. It also negatively affects the environment, human health and natural resources. Reducing construction wastes through 3R practices is a way towards sustainable waste management. The aim of this paper is to study on current construction waste management situation and the importance of waste reduction through 3R in Malaysia, particularly in Penang. Research methodology consists of interview and observation. Semi-structure interview section was conducted with officers in charge the Jelutong Landfill and participant observation was carried out at Jelutong Landfill and Illegal dumping area in order to obtain the current construction waste management situation in Penang. The paper contains findings from the synthesis of literatures, interview and field observations. Based on the information obtained from observation, the quantity of construction waste sent to Jelutong Landfill is increasing and landfill condition is getting worse compared to previous years. Besides that, it has also been found that there exist some illegal dumping areas of construction waste in Penang. The result indicated the implementation of reducing construction wastes through 3R is still low in among contractors in Penang. Therefore, construction contractors should play important role in reducing construction waste through 3R practices. Implementation of top-down approach and good governance is necessary to improve the effectiveness of reducing construction waste through 3R practice towards sustainable waste management.